Age-dependent increase of cytoskeletal components in sensory axons in human skin - Metzner, Klara; Darawsha, Omar; Wang, Mengzhe; Gaur, Nayana; Cheng, Yiming; Rödiger, Annekathrin; Frahm, Christiane; Witte, Otto W.; Perocchi, Fabiana; Axer, Hubertus; Grosskreutz, Julian; Brill, Monika S. (Frontiers in Cell and Developmental Biology, 2022)
Aging is a complex process characterized by several molecular and cellular imbalances. The composition and stability of the neuronal cytoskeleton is essential for the maintenance of homeostasis, especially in long neurites. Using human skin biopsies containing sensory axons from a cohort of healthy individuals, we investigate alterations in cytoskeletal content and sensory axon caliber during aging via quantitative immunostainings. Cytoskeletal components show an increase with aging in both sexes, while elevation in axon diameter is only evident in males. Transcriptomic data from aging males illustrate various patterns in gene expression during aging. Together, the data suggest gender-specific changes during aging in peripheral sensory axons, possibly influencing cytoskeletal functionality and axonal caliber. These changes may cumulatively increase susceptibility of aged individuals to neurodegenerative diseases.